2007
DOI: 10.1029/2006jd007562
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of surface solar irradiance induced by aerosols in a suburban region in northeastern China

Abstract: In the spring of 2005, a Sun photometer and a set of broadband pyranometers were installed in Liaozhong, a suburban region in northeastern China. Aerosol properties derived from Sun photometer measurements and aerosol‐induced changes in downwelling shortwave surface irradiances are analyzed in this paper. It is shown that the mean aerosol optical depth (AOD) at 500 nm is 0.63. The day‐to‐day variation of aerosol optical depth is dramatic, with a maximum daily AOD close to 2.0 and a minimum value close to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 39 publications
11
42
1
1
Order By: Relevance
“…Figure 9 shows scatter plots of the difference between ground SKYNET and Himawari-8 global radiation data sets with respect to the is consistent with those of previous studies showing that Fukue is usually characterised by thicker aerosols (Dim et al, 2013). Overall, these results are roughly in agreement with findings reported in modelling studies (Irie et al, 2017) and 20 previous observational results (e.g., Xia et al, 2007;Huttunen et al, 2014). Indeed, computations performed by a radiative transfer model under the usual conditions at Chiba showed that the direct radiative forcing efficiency at SZA of 50° is about -150 W/m 2 per AOD unit (Irie et al, 2017).…”
Section: Validations Under Clear-sky Conditionssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 9 shows scatter plots of the difference between ground SKYNET and Himawari-8 global radiation data sets with respect to the is consistent with those of previous studies showing that Fukue is usually characterised by thicker aerosols (Dim et al, 2013). Overall, these results are roughly in agreement with findings reported in modelling studies (Irie et al, 2017) and 20 previous observational results (e.g., Xia et al, 2007;Huttunen et al, 2014). Indeed, computations performed by a radiative transfer model under the usual conditions at Chiba showed that the direct radiative forcing efficiency at SZA of 50° is about -150 W/m 2 per AOD unit (Irie et al, 2017).…”
Section: Validations Under Clear-sky Conditionssupporting
confidence: 92%
“…Indeed, computations performed by a radiative transfer model under the usual conditions at Chiba showed that the direct radiative forcing efficiency at SZA of 50° is about -150 W/m 2 per AOD unit (Irie et al, 2017). A similar value (-146.3 W/m 2 ) was experimentally estimated from observations recorded by a CIMEL radiometer at Liaozhong (China) (Xia et al, 2007) and comparable estimates were highlighted for other AERONET stations around the world (Huttunen et al, 2014). 25…”
Section: Validations Under Clear-sky Conditionssupporting
confidence: 60%
“…120.7°E) (Xia, et al, 2007), but close to retrievals of long range transport of boreal forest smoke aerosols (Eck et al, 2003). The surface measurement of BC concentration and AAE at Tongyu, Northeast China, evidenced the long-range transport of the smoke layer from active fire sources (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Although work is ongoing to include aerosol effect in the algorithm, the current version does not take aerosols into account. Many previous studies estimated the aerosol impact on surface solar radiation (e.g., Xia et al, 2007;Cachorro et al, 2008;Di Biagio et al, 2009Papadimas et al, 2012;Huttunen et al, 2014). In particular, under clear-sky conditions, a daily mean direct aerosol forcing on surface global radiation between −8 and −64 W m −2 for East Asia (e.g., Table 1 in Kudo et al, 2010) and in the range −8 to −23 W m −2 for Japan (in the Kanto region) has been reported (Kudo et al, 2010).…”
Section: Himawari-8 Estimates Of Surface Downwelling Solar Radiationmentioning
confidence: 99%